Aesthetic capitalism - Fuente, Eduardo de la.; Murphy, Peter, 1956- (Social and Critical Theory, 2014)
Aesthetic Capitalism debates the social aesthetics of contemporary economic processes. The book connects modern cultural dynamics with the workings of contemporary capitalism. It explores art and the new spirit of capitalism; visual culture and the experience economy; aesthetics and organisations; the art of fiscal management; capitalism without myth; and architecture in the age of aesthetic capitalism. Contributors include: Peter Murphy, Eduardo de la Fuente, Antonio Strati, Ken Friedman, Dominique Bouchet, Anders Michelsen, David Roberts, Carlo Tognato